2020
DOI: 10.1016/j.cub.2020.03.032
|View full text |Cite
|
Sign up to set email alerts
|

MpFEW RHIZOIDS1 miRNA-Mediated Lateral Inhibition Controls Rhizoid Cell Patterning in Marchantia polymorpha

Abstract: Lateral inhibition patterns differentiated cell types among equivalent cells during development in bacteria, metazoans, and plants. Tip-growing rhizoid cells develop among flat epidermal cells in the epidermis of the early-diverging land plant Marchantia polymorpha. We show that the majority of rhizoid cells develop individually, but some develop in linear, one-dimensional groups (chains) of between 2 and 7 rhizoid cells in wild-type plants. The distribution of rhizoid cells can be accounted for within a simpl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 38 publications
8
46
0
Order By: Relevance
“…We here show successful PI staining of cell walls of M. polymorpha (Figure 11), in agreement with former reports (Delmans et al, 2017;Jones and Dolan, 2017;Thamm et al, 2020). Strong fluorescence was observed already after short incubation times of 10 min.…”
Section: Propidium Iodide For Cell Wall Stainingsupporting
confidence: 92%
See 1 more Smart Citation
“…We here show successful PI staining of cell walls of M. polymorpha (Figure 11), in agreement with former reports (Delmans et al, 2017;Jones and Dolan, 2017;Thamm et al, 2020). Strong fluorescence was observed already after short incubation times of 10 min.…”
Section: Propidium Iodide For Cell Wall Stainingsupporting
confidence: 92%
“…In the last decade, the liverwort Marchantia polymorpha has emerged as a powerful model system to study early land plant evolution due to its early evolutionary divergence in the land plant phylogenetic tree ( Shaw et al, 2011 ; Harrison, 2017 ; Morris et al, 2018 ). Research deploying M. polymorpha has led to a series of insightful studies on the functional evolution of abscisic acid (ABA, Lind et al, 2015 ; Eklund et al, 2018 ) and jasmonic acid (JA) signaling mechanisms ( Monte et al, 2018 , 2019 ; Peñuelas et al, 2019 ), plant immunity ( Carella et al, 2019 ; Gimenez-Ibanez et al, 2019 ), reproductive and vegetative development ( Flores-Sandoval et al, 2015 ; Proust et al, 2016 ; Jones and Dolan, 2017 ; Rövekamp et al, 2016 ; Otani et al, 2018 ; Westermann et al, 2019 ; Thamm et al, 2020 ) and cell division ( Buschmann et al, 2016 ). It offers the advantage of genetic and morphological simplicity in combination with its dominant haploid vegetative life phase, allowing for fast generation of knockout mutants and subsequent phenotypic analyses, irrespectively of time-consuming homozygous mutant generation ( Ishizaki et al, 2015b ).…”
Section: Introductionmentioning
confidence: 99%
“…Gemmae, mucilage cells, and rhizoids have a common feature in that they are formed from a single epidermal cell. It has been proposed that Mp FRH1 plays a role in the spatial specification of rhizoids via inhibition of Mp RSL1 in surrounding cells (Honkanen et al ., 2018; Thamm et al ., 2020); a similar system might regulate the spatial distribution of gemmae and mucilage cells in the gemma cup floor.…”
Section: Regulation Of Gemma Developmentmentioning
confidence: 99%
“…New Phytologist has recently been identified (Honkanen et al, 2018;Thamm et al, 2020). This demonstrated that the negative regulators of class 1 RSL genes, at least in liverworts, are different from those in A. thaliana where class 1 RSL genes are negatively regulated by a Class IV homeodomain-leucine-zipper protein, AtGL2 (Di Cristina et al, 1996;Bernhardt et al, 2003;Lin et al, 2015).…”
Section: Reviewmentioning
confidence: 99%
“…FEW RHIZOIDS1 (MpFRH1), a microRNA that acts as a negative regulator of the class 1 RSL gene in M . polymorpha , has recently been identified (Honkanen et al ., 2018; Thamm et al ., 2020). This demonstrated that the negative regulators of class 1 RSL genes, at least in liverworts, are different from those in A .…”
Section: Hornwort Developmentmentioning
confidence: 99%